Controlled diabetes amends oxidative stress as mechanism related to severity of diabetic retinopathy - Rania Fahmy (Nature Portfolio, 2021)
Abstract Oxidative stress is a well-accepted etiological mechanism that contributes to neuronal dysfunction. Role of oxidative stress as a mechanism of retinopathy in controlled type 2 diabetic patients was evaluated. Participants were divided into three groups: Group 1 as 30 normal eyes of 15 subjects, Group 2 comprised 24 eyes of 12 diabetic patients without retinopathy and Group 3 comprised 23 eyes of 12 diabetic patients with different grades of retinopathy (8 eyes with maculopathy). A complete ophthalmological examination was performed. Oxidative stress markers were measured in blood. Macular thickness was different in all quadrants among all groups and showed a tendency to increase in Group 3 due to diabetic retinopathy with insignificant changes in parapapillary retinal nerve fiber layer thickness although thinning was noted also with retinopathy. Non-significant differences in GST and lipid peroxide levels were observed between the three studied groups, whereas vitamin C and GSH levels were higher in diabetic patients when compared to those in controls. As oxidative stress, hyperglycemia and local inflammation are involved in the pathogenesis of DR, the present study proved that the progressive damage can be retarded in controlled type 2 diabetic patients using different treatment modalities that abated oxidative stress.